O reconhecimento da paternidade por socioafetividade e seus efeitos jurídicos - Rodrigues, Emerson Alexandre Molina (2007)
The Federal Constitution of 1988 developed an important change in Family Law trought the begining of equality between the offspring. It has introduced to the legal sistem a change in familie relashionship values, that affected a new kind of parenthood, born from affection, the relevant point questioned in this project. Thus, it is important to discuss a new approach of the united offspring sistem s repercussion in the national legal order, and discuss its effects in estate and personal rights. It is fundamental to mention the position of brasilian authors in this matter, as well as the legal decisions that make the current understanding of the local Courts of Law, in order to find the success of the subject in the present bibliographic research